USE OF EDUCATIONAL TECHNOLOGIES IN PREPARING FUTURE TEACHERS FOR INNOVATIVE ACTIVITY - Nurmakhanovna , Amirkhanova Diana (PT. Antis International Publisher, 2024)
The modern education system requires the formation of a creative person who can independently receive new information, evaluate it and draw appropriate conclusions